PENGARUH TAX AVOIDANCE DAN LEVERAGE TERHADAP COST OF DEBT PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Handayani, Vivi; Das, Nidia Anggreni; Sukraini, Juita (LP2M Universitas Bina Bangsa, 2025)
Indonesia's economy is largely driven by increased household consumption and one of the fastest-growing industries is the food and beverage industry. Sales growth was driven by increased personal income and increased spending on food and beverages, mainly from the growing number of middle-class consumers. As a result, it is also an industry where local companies are very ambitious and have grown into successful global exporters. At the same time, the internationalization of local cuisine is a major opportunity for foreign companies to sell their products to Indonesia consumers, who are increasingly open to new foods and flavors. The purpose of this study is to determine the Effect of Tax Avoidance on the Cost of Debt in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2022. The method carried out in this study is a quantitative method with an associative approach. Meanwhile, to analyze the data obtained, classical assumptions were used consisting of (normality test, multicollinearity test, heteroscedasticity test, and heteroscedasticity test, multiple linear regression analysis, determination coefficient analysis and hypothesis test using significance tests (T test and F test). The results of the study show that individually Tax Avoidance (X1) does not have a significant effect on Cost Of Debt (Y), Leverage (X2) has a significant effect on Cost Of Debt, Tax Avoidance Variable (X1), leverage (X2) together have a significant effect on Cost Of Debt (Y).